Socio-Economic Impediments in Usage of Modern Mechanized Technological Ideals in Agriculture Sector: A Case Study of District Lodhran, Punjab-Pakistan - Ashraf, Muhammad Umair; Asif, Muhammad; Talib, Azlizan; Ashraf, Asfa; Nadeem, Muhammad Sajid; Ahmad Warraich, Imtiaz (Elite Scientific Forum, Pakistan, 2019)
The process of adopting modern mechanized technological ideals encompasses certain aspects such as demographic characteristics, economic stability and societal acceptance regarding advanced methods of farming. The core objective of this research was to explore the role of socio-economic impediments in usage of modern mechanized technological ideals in agriculture sector of district Lodhran, Punjab-Pakistan. The present research was descriptive in nature and structured interview schedule was used to collect the data. A total of 200 small and large-scale farmers were selected through multi-stage sampling technique. Results revealed that 80% of the farmers do not adopt modern technological ideals due to economic instability, 35% of farmers reported that no person came into their area for guiding and training them regarding modern machinery and 62.5 % stated that there were cultural barriers behind not coming of trainers. This study concluded that farmers perceived modern mechanism more beneficial for their fields, but socio-economic impediments were playing vital role in hindering the adoption of modern mechanized ideals